Factibilidad financiera de la industrialización de los subproductos de banano para la finca la Villa. - Nugra Pineda, Milena Lissette; Chato Panta, Shirley Madelaine (Machala : Universidad Técnica de Machala, 2024)
The “La Villa” farm is located in Pasaje, El Oro, an area where banana cultivation is one of the main agricultural activities. The objective of this document is to determine the financial feasibility of the industrialization of banana byproducts in “La Finca La Villa” focusing on profitability as a basis for taking advantage of waste and generating additional income. The methodology used was a non-experimental design, with a descriptive and explanatory quantitative approach with a scientific method, through the observation technique and an interview with the owner and accountant of the farm. As a result, it was obtained that the investment in the industrialization of banana by-products was USD 38,917.50, which includes the purchase of machinery, inputs, costs and expenses. In conclusion, it is obtained that the NPV amounts to USD 21.102,38 thousand with an IRR of 39.40%, which demonstrates that the project has a profitable feasibility for five years projected.
La finca “La Villa”, está situada en Pasaje, El Oro, una zona donde el cultivo de banano es una de las principales actividades agrícolas. El objetivo del presente documento es determinar la factibilidad financiera de la industrialización de los subproductos de banano en “La Finca La Villa” enfocándose en la rentabilidad como base para aprovechar los residuos y generar ingresos adicionales. La metodología utilizada fue un diseño no experimental, con un enfoque cuantitativo de tipo descriptivo y explicativo con un método científico, mediante la técnica de observación y una entrevista al dueño y la contadora de la finca. Como resultado se obtuvo que la industrialización de subproductos de banano la inversión fue de USD 38.917,50 que incluye la compra de maquinaria, insumos, costos y gastos. Como conclusión se obtiene que el VAN asciende a USD 21.102,38 mil con un TIR de 39.40%, lo que demuestra que el proyecto tiene una factibilidad rentable para los cinco años proyectados.
Keywords: FACTIBILIDAD; FINANCIERA; INVERSIONES; BANANO